Penerapan pembelajaran diferensiasi pada pendidikan inklusi: studi kasus di sdn x kabupaten mojokerto - Ainur Rofiqi; Fauziyah Fauziyah; Slamet Arifin; Ratna Ekawati (Universitas Sebelas Maret, 2025)
Inclusive education reflects a national commitment to guaranteeing every individual’s right to education, yet its implementation continues to face challenges. This study examines the complexity of implementing differentiated instruction at SDN X, Mojokerto Regency, as a representation of inclusive practices in public elementary schools. Using a case study design, the research involved classroom teachers, the principal, and parents as participants. Data were collected through validated interviews and classroom observations, then analyzed using data triangulation based on the Miles and Huberman framework. The findings reveal that differentiated instruction has been implemented through flexible content modification, the use of varied learning media, and adjustments to learning time. However, its implementation remains suboptimal due to the absence of Special Education Teachers and the lack of an inclusive education team. Theoretically, the study indicates that the effectiveness of differentiated instruction in inclusive settings depends not only on teachers’ pedagogical competence but also on strong collaboration between schools and parents through the Individualized Education Program (IEP). Practically, the findings highlight the need to strengthen structural support by providing Special Education Teachers, establishing an inclusion team, enhancing teacher capacity, and fostering sustained collaboration with relevant stakeholders to ensure more effective and sustainable implementation of differentiated instruction